The answer should be B and A
<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3
Answer:
Let's solve your equation step-by-step.
3 / 4 y = 9
Step 1: Multiply both sides by 4/3.
(4 / 3 ) * ( 3 / 4 y ) = ( 4 / 3 ) * ( 9 )
y = 12
Answer:
y = 12
<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3
Insert 12 to the y value:
3 / 4 ( 12 ) = 9
9 = 9
True
<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3<3
Let y=x+6 be equation 1...
Replace equation 1 in equation 2
X+6 =-2x-3
X+2x = -3 -6
3x = -9
X = -3
F(x)=
to solve for the inverse of a function you do 4 steps:
1. subsitute f(x) with y
2. switch y and x places
3. solve for y
4. subsitute y with f⁻¹(x)
so we have
f(x)=
subsitute f(x) with y
y=
switch x and y
x=
solve for y
x=
cube both sides
=y+2
subtract 2 from both sides
=y
subsitute y with f⁻¹(x)
f⁻¹(x)=
the answer is f⁻¹(x)=
Answer:
(1,9)
Step-by-step explanation: